Bio-adsorption properties of Rhodamine B from aqueous solution onto natural camphor tree leaf powder. Issue 32 (8th July 2016) - Gan, Huihui; Zhang, Huining; Cai, Jiawei; Jin, Huixia; Zhang, Kefeng
Abstract: The potential of camphor tree leaf powder (CALP) to remove Rhodamine B (RhB) from aqueous solution was evaluated. The CALP was characterized by the scanning electron microscope and Fourier transform infrared technique, respectively. The effects of contact time, initial RhB concentrations, solution pH, and strength of the coexisting cations and anions upon the RhB adsorption were evaluated. The CALP had buffering action on the RhB/CALP system to maintain the solution pH in the range of 7. The Langmuir, Freundlich, and Koble–Corrigan isotherm models were used to analyze the adsorption behavior and the Koble–Corrigan isotherm fits the equilibrium data best ( R 2 > 0.99). The kinetic studies indicated that the adsorption process was fitted well with the pseudo-second-order model with rate constants ( k 2 ) in the range of 0.2586–3.0489 g/mg/min, suggesting that the adsorption might be a chemisorption process. The thermodynamic parameters indicated that adsorption process was feasible and spontaneous.